2006
DOI: 10.1063/1.2336432
|View full text |Cite
|
Sign up to set email alerts
|

Determination of chiral asymmetries in the valence photoionization of camphor enantiomers by photoelectron imaging using tunable circularly polarized light

Abstract: An electron imaging technique has been used to study the full angular distribution of valence photoelectrons produced from enantiomerically pure molecular beams of camphor when these are photoionized with circularly polarized light. In addition to the familiar beta parameter, this provides a new chiral term, taking the form of an additional cosine function in the angular distribution which consequently displays a forward-backward electron ejection asymmetry. Several ionization channels have been studied using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
192
0
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 109 publications
(201 citation statements)
references
References 43 publications
4
192
0
5
Order By: Relevance
“…Conversely, to obtain the PECD of the deeper--lying orbitals, we have obtained the electron images correlated In addition, the double imaging coincidence scheme permits removing common background impurities such as water, N2, O2, which would increase the achiral content in the total signal used for normalization and therefore decrease the observed PECD. Overall, the procedure dramatically increases the signal--to--noise ratio with respect to previous non--coincident data 36,40 recorded for camphor and fenchone, as evidenced with the low error bars and excellent mirror behavior. Indeed, in Figure 1c the PECD baseline, BL, barely deviates from the ideal zero value over the whole kinetic energy range, with a weighted mean value of 0.0003 ± 0.0005.…”
Section: Camphor Datamentioning
confidence: 67%
See 4 more Smart Citations
“…Conversely, to obtain the PECD of the deeper--lying orbitals, we have obtained the electron images correlated In addition, the double imaging coincidence scheme permits removing common background impurities such as water, N2, O2, which would increase the achiral content in the total signal used for normalization and therefore decrease the observed PECD. Overall, the procedure dramatically increases the signal--to--noise ratio with respect to previous non--coincident data 36,40 recorded for camphor and fenchone, as evidenced with the low error bars and excellent mirror behavior. Indeed, in Figure 1c the PECD baseline, BL, barely deviates from the ideal zero value over the whole kinetic energy range, with a weighted mean value of 0.0003 ± 0.0005.…”
Section: Camphor Datamentioning
confidence: 67%
“…In the higher resolution PES recorded by Rennie et al 51 with a hemispherical analyzer the electronic band structure is slightly more marked and seen to correlate with the PECD changes. The OVGF calculations published by Rennie et al also correspond to the observed oscillations, which highlights the enhanced sensitivity of PECD to electronic structure when compared to usual observables such as ionization cross--sections -even in the case of congested electronic bands as already observed in camphor 36 and glycidol 13 .…”
Section: Camphor Datamentioning
confidence: 88%
See 3 more Smart Citations